Memperkuat Rasa Nasionalisme pada Anak Sekolah Dasar dan Remaja Melalui Gotong Royong dan Menjelaskan tentang Hak dan Kewajiban Anak di Rumah, di Sekolah dan di Masyarakat di Desa Hurung Jilok Kecamatan Sosa Julu Kabupaten Padang Lawas - Nur Hikmah Nasution; Nur Hakimah Akhirani Nasution (Khidmat Almujtamae: Jurnal Pengabdian Masyarakat, 2023)
Provide understanding and knowledge to elementary school children about their rights and obligations both at school, at home and in the community in Hurung Jilok village, Sosa Julu sub-district, Padang Lawas district, and also provide awareness to the community and young people about how to maintain cleanliness in the graveyard. The activity went on smoothly with enthusiastic greetings from elementary school children, school principals and teaching staff, the community and teenagers who took part in this activity demonstrating the results of a good understanding of strengthening a sense of nationalism. Provide understanding and knowledge to elementary school children about their rights and obligations both at school, at home and in the community. The spirit of elementary school children in understanding their rights and obligations at school, at home and in society.